The Effect of Competence on Performance With Training as an Intervening Variable in Regional Apparatus North Sumatra Province - Neny Prestiany; Kiki Farida Ferine (International Journal of Society and Law, 2024)
The purpose of this study is to find out and analyze the influence of Competency on Employee Performance mediated by Training for Employees of the North Sumatra Human Resources Development Agency. This research was carried out at the North Sumatra Human Resources Development Agency. The type of research is quantitative associative. The sample in this study is 107 employees of the North Sumatra Human Resources Development Agency. The sampling technique in this study uses a saturated sample so that the entire population will be a sample of 107 people. The results of the study show that Competence has a significant influence on Employee Performance as shown by a T-Statistic value of 4,572 > 1.96 and a P Value of 0.000 < 0.05. In the effect of Competency on Training, data on T-Statistical values were obtained from 1,180 < 1.96 and P-Value values of 0.238 > 0.05 or no effect of Competence on Training. Training had a significant effect on Employee Performance with a T-Statistic value of 2,190 > 1.96 with a P-Value of 0.029 < 0.05. In the indirect influence, the results show that training does not have a role as an intervening variable that will explain the relationship between Competency and Employee Performance of Employees of the North Sumatra Human Resources Development Agency. This shows that improvements in Competencies will not be able to improve Training, which in the end will also not be able to contribute to improving the Performance of Employees of the North Sumatra Human Resources Development Agency.